Medieval Britain and Ireland in 2014. (1st January 2015) - Naylor, John; Vitali, Tiziana; Gleeson, Patrick; Ó Carragáin, Tomás
Abstract : This section of the journal comprises two core sets of reports linked to work in 2014: on finds and analyses relating to the Portable Antiquities Scheme (PAS) and on site-specific discoveries and reports in medieval Britain and Ireland (MB&I), with a selection of highlighted projects. For the PAS report, reviews on coin and non-coin finds and on specific research angles are presented. For MB&I, the Society is most grateful to all contributors (of field units, museums, universities, developers, specialist groups and individuals) who have provided reports on finds, excavations, field-surveys and building analyses for 2014. For MB&I, see below for the format and content of the Fieldwork Highlights section and for contact details of the compilers. The annual Specialist Groups Reports appear in the Society's Newsletter .